Creating an appropriate competitive performance by innovation and competitive firm strategy (a study of foods and beverage industry in Makassar) - Abdul Rakhman Laba (Journal of Economics, Business, and Accountancy Ventura, 2014)
This study attempts to investigate the effect of innovation, cost strategy and delivery system on the quality and flexibility in achieving high firm’s performances in foods and drinks industry. This research was undertaken in Makassar on 120 firms which are represented by staff, managers, directors, owners and HRD, using questionnaires. Types of firms which participated in the survey are individually owned firm, sole proprietary, commanditer and corporation which operate in the several Makassar suburb. The data were collected and analyzed by implementing Structural Equation Modeling. It shows that innovation has affected quality  significantly. Cost strategy has also affected quality significantly and also cost strategy has affected flexibility significantly. However, the cost strategy did not affect quality. Beside, quick delivery system did not affect the flexibility. The quality did not affect firm performances whereas the flexibility has affected firm performance significantly.